Plant Alkaloids as an Emerging Therapeutic Alternative for the Treatment of Depression - Perviz, Sadia; Khan, Haroon; Pervaiz, Aini (Frontiers in Pharmacology, 2016)
Depression is a heterogeneous mood disorder that has been classified and treated in a variety of ways. Although, a number of synthetic drugs are being used as standard treatment for clinically depressed patients, but they have adverse effects that can compromise the therapeutic treatments and patient's compliance. Unlike, synthetic medications, herbal medicines are widely used across the globe due to their wide applicability and therapeutic efficacy associated with least side effects, which in turn has initiated the scientific research regarding the antidepressant activity. This review is mostly based on the literature of the last decade, aimed at exploring the preclinical profile of plant-based alkaloids (the abundant secondary metabolite) as an emerging therapy for depression.